Impact of preoperative treatment of osteoporosis on re-operations, complications and health care utilization in patients undergoing thoraco-lumbar spine fusions. A 5-year national database analysis. (November 2021) - Sharma, Mayur; John, Kevin; Dietz, Nicholas; Jain, Nikhil; Madrigal, Fabian Carballo; Wang, Dengzhi; Ugiliweneza, Beatrice; Drazin, Doniel; Boakye, Maxwell
Highlights: OP has significant impact on health care utilization following TL fusions. We studied the impact of preoperative treatment of OP on outcomes at long-term follow-up. The majority of patients did not receive preoperative treatment for OP. Preoperative treatment of OP had no impact on outcomes at index hospitalization. Preoperative treatment for OP had no impact on reoperation rates 12-, 24- and 60 months. Abstract: Objective: Identify the impact of preoperative treatment of Osteoporosis (OP) on reoperation rates, complications and healthcare utilization following thoraco-lumbar (TL) spine fusions. Materials and Methods: We used ICD9/10 and CPT codes to extract data from MarketScan (2000–2018). Patients were divided into two groups based on preoperative treatment of OP within one year prior to the index spinal fusion: medication (m-OP) cohort and non-medication (nm-OP) cohort. Outcomes (re-operation rates, re-admission, complications, healthcare utilization) were analyzed at 1-, 12-, 24- and 60-months. Results: Of 3606 patients, 65% (n = 2330) of patients did not receive OP medications (nm-OP). At index hospitalization, there were no difference in LOS (median nm-OP: 3 days vs. m-OP:4 days), discharge to home (nm-OP 80% vs. m-OP 75%) and complications (nm-OP 13% vs. m-OP 12%). Reoperation rates were not different among the cohorts at 1- (nm-OP 5.7% vs. m-OP 4.2%), 2- (nm-OP 9.4% vs. m-OP 7.8) and 5 years (nm-OP 16.9% vs. m-OP 14.8%). Patients in m-OP cohort incurred higher overall median payments at 1 year ($17, 866 vs. $ 16, 010), 2 years ($38, 634 vs. $34, 454) and 5 years ($94, 797 vs. $91, 072) compared to nm-OP cohort. Conclusion: Preoperative treatment of OP had no impact on complications, LOS, discharge disposition following TL fusions at index hospitalization. Similarly, no impact of preoperative treatment was noted in terms of reoperation rates at 12-, 24- and 60 months following the index spine fusion. Patients who received preoperative treatment for OP incurred higher health care utilization at 12-, 24- and 60 months following surgery.